Factors affecting antibody responses to immunizations in infants born to women immunized against pertussis in pregnancy and unimmunized women: Individual-Participant Data Meta-analysis. Issue 44 (22nd October 2021) - Abu-Raya, Bahaa; Maertens, Kirsten; Munoz, Flor M.; Zimmermann, Petra; Curtis, Nigel; Halperin, Scott A.; Rots, Nynke; Barug, Daan; Holder, Beth; Rice, Thomas F.; Kampmann, Beate; Leuridan, Elke; et al.
Abstract: Background: Exploring factors that affect immune responses to immunizations in infants born to women immunized with tetanus-diphtheria-acellular-pertussis (Tdap) in pregnancy compared with unimmunized women is important in designing immunization programs. Methods: Individual-participant data meta -analysis of 8 studies reporting post-immunization immunoglobulin G (IgG) levels to vaccine antigens in infants born to either women immunized with Tdap in pregnancy or unimmunized women, using mixed-effects models. Results: In infants of Tdap-immunized women, two-fold higher levels of anti-pertussis toxin (PT) and anti-diphtheria-toxoid (DT) IgG pre-primary immunization were associated with 9% and 10% lower post-primary immunization levels, (geometric mean ratio [GMR], PT: 0.91; 95% CI, 0.88–0.95, n = 494, DT: 0.9; 0.87–0.93, n = 519). Timing of immunization in pregnancy did not affect post-primary immunization anti- Bordetella pertussis, anti-tetanus-toxoid (TT) and anti-DT IgG levels. Spacing of infant immunization did not affect post-primary immunization anti- B. pertussis and anti-DT levels. In infants of Tdap-immunized women, two-fold higher levels of anti-PT and anti-filamentous haemagglutinin (FHA) IgG pre-primary immunization were associated with lower post-booster immunization levels, (GMR, PT: 0.91; 0.85–0.97, n = 224, FHA: 0.92; 0.85–0.99, n = 232). Timing of immunization in pregnancy did not affect post-booster immunization anti- Bordetella pertussis, anti-tetanus-toxoid (TT) and anti-DT IgG levels. Spacing of infant immunization did not affect post-booster immunization anti-PT, anti-pertactin (PRN), anti-TT and anti-DT IgG levels. In infants of unimmunized women, two-fold higher IgG levels of some vaccine antigens pre-primary immunization were associated with 8–17% lower post-primary immunization levels (GMR, PT 0.92, 95% CI:0.88–0.97, n = 373; FHA:0.88, 95% CI:0.85–0.92, n = 378; PRN:0.84, 95% CI:0.81–0.88, n = 367; TT:0.88, 95% CI:0.83–0.93, n = 241; DT: 0.83, 95% CI:0.79–0.87, n = 278). Two-fold higher levels of anti-FHA IgG pre-primary immunization were associated with 8% lower post-booster immunization levels (GMR, 0.92; 95% CI: 0.86–0.99, n = 138). Discussion: Increased IgG levels pre-primary immunization is associated with reduced post-primary and post-booster immunization levels for some antigens in infants of women immunized or unimmunized in pregnancy, but their clinical significance is uncertain.